Komunikasi Interpersonal Remaja Masjid Al Azhar dalam Membina Akhlak Generasi Muda Islam di Kecamatan Nibung Hangus Kabupaten Batubara - Ismail, Ismail Nasution (Al-Manaj : Jurnal Program Studi Manajemen Dakwah, 2022)
In 2014, Nibung Hangus District, Batubara Regency was still very far behind in terms of Islam. Several years ago, Nibung Hangus Sub-District, Batubara Regency, there were still no recitation activities for teenagers and mothers, there was no commemoration of Islamic holidays, and there was still no Al-Qur'an Education Park (TPA), and the mosque building was still very simple. Research is a qualitative scientific method research often used and carried out by a group of researchers in the field of social sciences. The results of the discussion are the effectiveness of the management of the youth organization of the Al Azhar mosque in building interpersonal communication with adolescents in Nibung Hangus District, Batubara Regency, namely greeting first, asking how teenagers are, dialogue, telling stories and advising. There are 2 supporting factors for interpersonal communication between the management of the youth organization of the Al Azhar mosque and adolescents in moral development in Nibung Hangus District, Batubara Regency, namely communication (in the form of advice, directions, and the like) carried out by the management of the Al Azhar mosque youth organization does not seem to force teenagers, so that teenagers do not feel too tense when they receive guidance and coaching and the management of the youth organization of the Al Azhar mosque as coaches already know the background, personality and daily life of teenagers. Meanwhile, interpersonal communication constraints between the administrators of the youth organization of the Al Azhar mosque and adolescents in moral development in the Nibung Hangus District, Batubara Regency, are adolescents who feel bored at the youth recitation of the Al Azhar mosque and adolescents who do not care about advice and moral guidance from the administrators of the youth organization of the Al Azhar mosque, District Nibung Scorched Coal District.